2006
DOI: 10.1108/08876040610704883
|View full text |Cite
|
Sign up to set email alerts
|

Online service failure, consumer attributions and expectations

Abstract: Purpose -The purpose of this paper is to examine the differences in consumers' attributions of blame for service failures and its affect on their expectations for recovery in both online and offline settings. Design/methodology/approach -A sample of non-student adults participated in a 2 (service type) by 2 (shopping medium) experimental design testing the affects of on-and offline shopping on consumers' attributions of blame for a service failure. Specifically, regression is employed to test the effects of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 17 publications
9
115
2
Order By: Relevance
“…These arguments are consistent with findings concerning the drawbacks of repeated service failures and ineffective recovery strategies (Bickle, 2010;Harris, et al, 2006). For example, Bickle (2010) found out that whenever a customer is dissatisfied with an item of clothing, it is assumed that they either blame themselves for choosing the wrong size; or blame the company for having a different size system.…”
Section: Process Failuressupporting
confidence: 71%
See 1 more Smart Citation
“…These arguments are consistent with findings concerning the drawbacks of repeated service failures and ineffective recovery strategies (Bickle, 2010;Harris, et al, 2006). For example, Bickle (2010) found out that whenever a customer is dissatisfied with an item of clothing, it is assumed that they either blame themselves for choosing the wrong size; or blame the company for having a different size system.…”
Section: Process Failuressupporting
confidence: 71%
“…From these findings, it was noted that consumers felt frustrated and anxious amongst other negative emotions when clothing they ordered online had not arrived. Harris, et al (2006) support the notion that consumers expect compensation after being inconvenienced by a service provider. By communicating how and when consumers may expect their products on a regular basis allows them to feel that the company is respectful of their time and purchase.…”
Section: Managerial Implicationssupporting
confidence: 55%
“…Following an on-line service failure, an on-line service recovery (i.e., tangible compensation and apology offered via e-mail) led to higher perceptions of distributive justice than off-line recovery (i.e., a phone conversation with a company representative). This finding is consistent with prior research suggesting that consumers might be less demanding with on-line recovery efforts (Harris et al, 2006b). Yet, it is important to note that the tangible compensation was not sufficient to restore consumers' distributive fairness in Study 2 (mean ratings uniformly below the neutral point of four).…”
Section: Discussionsupporting
confidence: 92%
“…Such attributions are a self-serving attempt for customers to protect their self-esteem (Harvey et al 2014;Miller and Ross 1975). However, it has been found that customers attribute failure to themselves in situations where they have utilized self-service technology (SST) or technology-enabled services (Harris, Mohr, and Bernhardt 2006;Heidenreich et al 2015;Zhu et al 2013). In these studies, failure was studied in the form of technical glitches, which are routine or expected (e.g.…”
Section: Attribution Theorymentioning
confidence: 98%
“…Heidenreich et al (2015) use a technology-based service for rail/flight ticket booking which considers booking interruption (again, a technical glitch) as failure. Harris, Mohr, and Bernhardt (2006) use a situation in which respondents face failure when they perform an online bank transfer. Although such technologyenabled services are "highly interactive," they cover only limited elements of co-creation (Bolton and Saxena-Iyer 2009).…”
Section: Attribution Theorymentioning
confidence: 99%